A Case of Hypotonia-Cystinuria Syndrome With Genito-Urinary Malformations and Extrarenal Involvement - Taroni, Francesca; Capone, Valentina; Berrettini, Alfredo; De Marco, Erika Adalgisa; Manzoni, Gian Antonio; Montini, Giovanni (Frontiers in Pediatrics, 2019)
Hypotonia-Cystinuria syndrome (HCS) is a rare disease, caused by a mutation in two contiguous genes (SLC3A1 and PREPL) localized on chromosome 2p21, and it is characterized by both renal involvement with cystine stones and nervous involvement with hypotonia. We here describe a 2 years old child with HCS associated with other clinical features as congenital anomalies of kidney and urinary tract (primary obstructed megaureter, POM), cryptorchidism and cardiac involvement (patent foramen ovale with atrial septum aneurysm). To the best of our knowledge, cryporchidism and POM have never been reported before in patients with HCS. Moreover, a cardiac involvement has been described only in another case of HCS that, interestingly, presents the same genetic abnormalities as our patient. The diagnosis of HCS can be difficult because neurological signs are aspecific and kidney stones are commonly absent during the first months of life. A better understanding of the complete clinical scenario associated with HCS can help clinicians suspect, diagnose and treat HCS earlier with a positive influence on both neurological and renal outcome.